Empowering self-care through patient education in heart failure patients: A multimodal approach comprising of P-PILs, videos, and personalized advice - Anu Philip; Chakrakodi Shashidhara Shastry; Muzhuvanchery Kesavan Unnikrishnan; Basavaraj Utagi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Heart failure (HF) patients, in developing countries like India, have limited access to information regarding their health/disease state. To identify patient problems and patient expectations through focused group discussions (FGD) and develop a multimodal educational tool consisting of a pictogram-based patient information leaflet (P-PIL), HF video, and personalized counseling (PC) for HF patients. MATERIALS AND METHODS: Based on the results of the FGD with stakeholders, we developed, validated, and tested educational tools such as P-PIL and HF videos and personalized counseling for enhancing patient education. RESULTS: FGD identified major patient-related barriers, and we developed and validated P-PIL and HF videos. Ninety heart failure patients participated in user testing knowledge assessment. The mean scores in knowledge significantly increased from 39.37 to 85.18 (P < 0.001), with 95% of patients favoring P-PIL for its layout design and content. P-PIL, HF videos, and personalized counseling together enhanced patient awareness and self-care, indicating positive healthcare outcomes in HF. CONCLUSION: A well-developed and validated PIL can be reinforced by videos and personalized counseling and enhancing knowledge levels in HF patients which eventually translates to better outcomes.